1972
DOI: 10.1085/jgp.59.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of Sodium Transport in Frog Skin

Abstract: Studies were made of the dependence of the rate of oxygen consumption, J , on the electrical potential difference, A,, across the frog skin. After the abolition of sodium transport by ouabain the basal oxygen consumption was independent of /x. In fresh skins J, was a linear function of Alk over a range of at least --70 my. Treatment with aldosterone stimulated the shortcircuit current, Io, and the associated rate of oxygen consumption, Jro, and increased their stability; linearity was then demonstrable over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1

Year Published

1973
1973
1987
1987

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 20 publications
2
28
1
Order By: Relevance
“…4 and Table III show that a block of Na transport by removal of Na from the external solution induces a subsequent increase in JA and J,, when Na is returned to the external solution. This behavior, and the previous results of Vieira et al (19), (showing that accelerating Na transport by negative clamping lowers the subsequent value of Io and positive clamping induces the opposite effect) could be interpreted according to Eqs. A-1 and A-2, as a result of an alteration of the phenomenological coefficients LN,r and L, or of the affinity of the metabolic driving reaction or both.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…4 and Table III show that a block of Na transport by removal of Na from the external solution induces a subsequent increase in JA and J,, when Na is returned to the external solution. This behavior, and the previous results of Vieira et al (19), (showing that accelerating Na transport by negative clamping lowers the subsequent value of Io and positive clamping induces the opposite effect) could be interpreted according to Eqs. A-1 and A-2, as a result of an alteration of the phenomenological coefficients LN,r and L, or of the affinity of the metabolic driving reaction or both.…”
Section: Discussionsupporting
confidence: 83%
“…Essig and Caplan (6) have proposed a theoretical model for the active transport of a single cation coupled to a chemical reaction. The adequacy of this model to sodium transport was partially tested by Vieira et al (18) (19) in the skin of the frog Rana pipiens. They have shown that there is in short-circuited state a linear relationship between the rates of sodium transport and oxygen consumption, and that the rate of oxygen consumption is a linear function of the transepithelial electrical potential difference.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations